Experimental, numerical and analytic study of unconstrained melting in a vertical cylinder with a focus on mushy region effects. (September 2018) - Pan, Chunjian; Charles, Joshua; Vermaak, Natasha; Romero, Carlos; Neti, Sudhakar; Zheng, Ying; Chen, Chien-Hua; Bonner, Richard
Highlights: New findings on the mushy zone parameter in the enthalpy-porosity method. Explanations on numerical sinking phenomenon by the enthalpy-porosity method. An analytic solution that has good match with experiments is developed. Abstract: The enthalpy-porosity method is widely used in solving solid-liquid phase change problems that involve convection in the melt; however the influence of the required mushy zone parameter on the melting process has been largely overlooked. In this paper, further investigation of the mushy zone parameter is presented. The enthalpy-porosity method is the default model in Fluent for melting simulations. A comprehensive discussion of previously reported mushy zone parameter values is presented with a comparison to numerical and experimental results. In this paper, based on experimental validations of melting times, it is found that mushy zone parameters can be optimized based on relevant driving temperature differences. And despite the fact that the model cannot capture bulk solid sinking behaviors, numerical solid sinking behaviors by Fluent are still widely reported in the literature. Explanations and supporting numerical analysis are given for this seeming contradiction. Finally, an analytic solution for unconstrained sinking is developed. With the introduction of a tuning parameter to modify the viscosity of the mushy region in the bottom liquid layer, good agreement between the analytical model and experimental results is achieved. A linear correlation for the tuning parameter based on driving temperature differences is given.